2018
DOI: 10.1186/s12882-018-0943-0
|View full text |Cite
|
Sign up to set email alerts
|

Practice patterns in transitioning patients from chronic kidney disease to dialysis: a survey of United States nephrologists

Abstract: BackgroundThere are no guidelines for transitioning patients from chronic kidney disease stage 5 to hemodialysis. We conducted this study to determine if there are uniform patterns in how nephrologists transition patients to dialysis.MethodsWe designed an electronic survey with 39 questions and sent it to a database of practicing nephrologists at the National Kidney Foundation. Factors that were important for transitioning a patient to hemodialysis were evaluated, including medication changes on dialysis initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Despite the use of antihypertensives, pre‐dialysis SBP (150 ± 24 mmHg) was higher than recommended, a result usually consistent with other studies . These results could be influenced by the fact that patients did not use all the antihypertensive drugs prescribed prior to the HD session (either on their own or by medical advice) to reduce the risk of intradialytic hypotension and to facilitate ultrafiltration . Also, noncompliance with medications is likely a contributor to uncontrolled hypertension in HD patients …”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Despite the use of antihypertensives, pre‐dialysis SBP (150 ± 24 mmHg) was higher than recommended, a result usually consistent with other studies . These results could be influenced by the fact that patients did not use all the antihypertensive drugs prescribed prior to the HD session (either on their own or by medical advice) to reduce the risk of intradialytic hypotension and to facilitate ultrafiltration . Also, noncompliance with medications is likely a contributor to uncontrolled hypertension in HD patients …”
Section: Discussionsupporting
confidence: 77%
“…However, no current guideline addresses the management of hypertension in HD . A recent survey that included 160 U.S. practicing nephrologists found that the highest percentage of respondents prescribe CCAs (68%) because they consider it to be more effective in treating hypertension in dialysis patients, followed by BB (35%), ACE (32%), BRA (29%), and diuretics (25%) . Studies suggest that lower systolic and diastolic blood pressure with the use of antihypertensive drugs results in a 30% lower risk of cardiovascular events and mortality, but adequately controlled hypertension is observed in only 65% of hypertensive patients …”
Section: Discussionmentioning
confidence: 99%
“…The ways patients view and manage their disease(s), the actions taken (or not taken) and the underlying motivations, but also to a larger extent, their life experiences, are as essential in the definition of the care trajectory and must be investigated in a complementary manner. Moreover, the care trajectory is heavily influenced by the individual practices of the involved health professionals, and in our case, by the coordinated work of GPs and nephrologists [24]. One example might be difficulties to obtain a consultation with (or be referred to) a nephrologist in a reasonable interval of time.…”
Section: The Mixed Methods Design and Its Rationalementioning
confidence: 99%
“…Chronic kidney disease (CKD) is a chronic kidney injury caused by various causes of primary glomerulonephritis, secondary glomerulonephritis, diabetes, and hypertension. The main feature is the progressive deterioration or irreversible damage to the structure and function of the kidney [ 1 ]. In the early stages of CKD, patients may have no symptoms or only mild fatigue, low back pain, and nocturia.…”
Section: Introductionmentioning
confidence: 99%